Urban Interfaces: The Cartographies of Screen-Based Installations. (May 2017) - Verhoeff, Nanna
This article analyzes the way media technologies provide interfaces for the complexity of cities as historically layered, continuously changing, and intricately connected spaces. Following Branden Hookway and Alexander Galloway, I understand media interfaces as processes rather than objects. An interface is not something; it does something. I propose to focus on the way in which often temporary, mobile, and connected interfaces produce urban cartographies in the very act and process of navigation. This navigation constitutes a performative cartography of ambulant presence, fluid connectivity, and an inherent multiplicity of connections between locations and other subjects. In what follows, I examine a small collection of urban art projects that speak to this description and suggest that the interface's pursuits of connectivity, and the stakes and claims inseparable from these pursuits, produce and structure urban cartographies. The article then questions in what ways interfaces can create, not a threshold between two dimensions, but spatial transformations of a third kind.